If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44 + -3x = 7x + -6 Reorder the terms: 44 + -3x = -6 + 7x Solving 44 + -3x = -6 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 44 + -3x + -7x = -6 + 7x + -7x Combine like terms: -3x + -7x = -10x 44 + -10x = -6 + 7x + -7x Combine like terms: 7x + -7x = 0 44 + -10x = -6 + 0 44 + -10x = -6 Add '-44' to each side of the equation. 44 + -44 + -10x = -6 + -44 Combine like terms: 44 + -44 = 0 0 + -10x = -6 + -44 -10x = -6 + -44 Combine like terms: -6 + -44 = -50 -10x = -50 Divide each side by '-10'. x = 5 Simplifying x = 5
| 80=-16t^2+128t | | 3(2x-3)-4(7-2x)=-30 | | 1-8(x-2)=57 | | (1/3)2= | | 5(3+x)+2x=8+19x | | -z=110 | | 2x+10=3x+50 | | 7m+2=6m+8 | | 12b-9b=12 | | 3x+7=4x+-2 | | 19t=21 | | p=.18x^2+36x+4000 | | 146=6x-2(-7x-3) | | 4(5x-10)+6=5x+10 | | 6y+3=y+13 | | 6.1h=4.3-3.2h | | 6x-3=24x | | -12x=168 | | 14b-9b=10 | | 24x-6=3x | | y=10x-150 | | 24x-3=6x | | -2x+6=6x+2 | | 9(x-10)+6x=-8x+2 | | 5(k+2)+8(k+3)=-1 | | 3x-5=-45-1x | | 12=-2.7t^2+30t+6.5 | | 145x-6=7x | | 3(2q+1)=8q-2(q-2) | | 5(x+3)=8x-3x+7 | | 5x-4-2x+1=4 | | 5v^2+11v-2=0 |